Dolly Parton's Billy the Kid Makes it Big - Parton, Dolly; Perl, Erica S.; Haley, MacKenzie (New York : Penguin Workshop, 2023)
"French bulldog Billy the Kid was born with an ear for music. And not just any music. He loves barking to the beat of country music! So Billy sets out to Nashville to sing his heart out. But when he meets some big bullies at the Battle of the Bow-wows, Billy worries he's barking up the wrong tree. He'll need his favorite songs ('Jowlene' and 'I Will Pawlways Love You,' of course), a group of scrappy new friends, and his favorite country music star to regain self-confidence and be the star he always knew he could be"--
Keywords: Dogs -- Juvenile fiction; Country music -- Juvenile fiction; Self-confidence -- Juvenile fiction; Bullying -- Juvenile fiction; Bullies -- Juvenile fiction; Friendship -- Juvenile fiction; Dogs -- Fiction; Country music -- Fiction; Self-confidence -- Fiction; Bullies and bullying -- Fiction; Friendship -- Fiction; Nashville (Tenn.) -- Juvenile fiction; Nashville (Tenn.) -- Fiction; Picture books